Prognostic Value of Radiotherapy and Chemotherapy in Stage I–III Merkel Cell Carcinoma - Bi, Aihong; Yang, Sifu; Ding, Yang; Yu, Yong; Zhan, Wenming; Song, Tao (Frontiers in Medicine, 2022)
Purpose: Merkel cell carcinoma (MCC) is a highly malignant cancer associated with dismal survival outcomes. Surgery is the cornerstone for the management of MCC, but the benefit of radiotherapy (RT) and chemotherapy (CT) is still controversial. We aimed to investigate the prognostic value of RT and CT in the management of stage I-III MCC patients using the Surveillance, Epidemiology, and End Results (SEER) database. Methods: Patients with a histopathological diagnosis of MCC between 2010 and 2016 were included. The primary endpoint of this study was overall survival (OS). The prognostic significance for OS was analyzed by Cox proportional hazard regression model. Results: A total of 1,691 patients were identified in the SEER database. Over half of the patients had received RT (56.7%), and 9.8% of the patients were documented to have received CT. The median OS for the entire cohort was 66.0 months, and the 5-year OS rate was 53.8%. In the multivariate analysis, receiving RT was associated with significantly improved OS (P < 0.001), while receiving CT significantly negatively impacted OS (P = 0.010). In stage III patients who underwent treatment based on surgical resection, RT was still demonstrated to be a positive factor (P = 0.002), while CT had no significant association with OS in the univariate analysis (P = 0.295). Conclusions: The current data in the SEER database are consistent with earlier studies supporting the benefit of adjuvant RT for stage I-III MCC patients, but caution should be taken regarding the routine use of CT. For stage III MCC patients, the value of adjuvant CT needs to be confirmed in future studies.